Enhancing Electrochemical Cells Performance with Modified Ionic Liquids and Deep Eutectic Solvents using Titanium Dioxide Nanoelectrodes- Graphite - Hasan, Bassam Baqer; Salman, Taghried Ali; Ayal, Asmaa Kadim (Iraqi Journal of Science, 2024)
Ionic liquids (ILs) and deep eutectic solvents (DESs) have been found to be highly effective as electrolytes in TiO2 NTAs-graphite cells when combined with additives that enhance conductivity by reducing the viscosity of these liquids. The presence of CaCl2.6H2O: Acetamide DES with DI water as an additive resulted in a cell voltage of 1.31V and an internal resistance of 19 ohm. This can be attributed to the concentration and quality of the ionic species. The cells exhibited an interesting response to the AlCl3-chloroacetamide IL with dichloromethane DCM as an additive, with a cell voltage of 1.81V and an internal resistance of 5.0 ohm. Once again, this is influenced by the quality and concentration of the ionic species. Furthermore, the cells demonstrated thermal stability during the charging and discharging processes. Additionally, the surfaces of the TiO2 NTAs electrodes were examined, along with the impact of the IL and DES on these electrodes, using SEM and EDXA equipment.